Singapore property tax law as it stands: The Rebus Sic Stantibus principle and the statutory formula - OOI, Vincent (Institutional Knowledge at Singapore Management University, 2020)
The Singapore jurisprudence appears to have adopted the proposition that the rebus sic stantibus principle is to be disapplied where section 2(3) of the Singapore Property Tax Act (“PTA”) (the “Statutory Formula”) is applied. This article argues that this proposition perhaps ought to be stated more precisely. The principle is only disapplied where section 2(3)(b) is applied because it would run contrary to the statutory fiction imposed by section 2(3)(b) that the land is to be valued as if it were vacant land. There should be no disapplication of the principle where section 2(3)(a) is applied due to the absence of any such conflict. In practice, the Chief Assessor and courts appear to have implicitly recognised this. However, the recent Swiss Club case might have departed from this by disapplying the principle when section 2(3)(a) was applied. This provides an opportune moment to clarify the underlying proposition and its rationale.